The Debate on the Grace Period in Appealing Cases Against the State Administrative Court - Monica, Lamira Sekar; Rahman, Malik Akbar Mulki; Windiasari, Windiasari (Indonesian State Law Review (ISLRev), 2023)
This study delves into the nuanced discourse surrounding the grace period concerning appeals against decisions rendered by the State Administrative Court (Pengadilan Tata Usaha Negara, PTUN) in Indonesia. Against the backdrop of Indonesia’s evolving legal landscape and commitment to administrative justice, this research critically examines the existing grace period and its implications for litigants, judicial efficiency, and the broader pursuit of fairness. The study considers perspectives from legal scholars, practitioners, and policymakers within the Indonesian context, assessing the necessity and efficacy of the current grace period. Additionally, the research explores comparative legal frameworks, offering insights into how other jurisdictions navigate the delicate balance between finality in administrative decisions and ensuring access to justice. Through case studies and empirical analysis, the study evaluates the practical impact of the grace period on the Indonesian legal system. It aims to identify potential areas for improvement and inform discussions on legal reforms that align with Indonesia’s commitment to enhancing governance, rule of law, and the overall administration of justice. By engaging with Indonesia's unique administrative and legal challenges, this research contributes not only to the academic discourse but also holds practical implications for legal practitioners, policymakers, and stakeholders involved in shaping the country’s legal framework. Ultimately, the study aspires to be a catalyst for informed discussions and potential reforms that will strengthen the Indonesian State Administrative Court system, fostering a more equitable and efficient dispensation of administrative justice.